Analisis Peremajaan Kawasan Kumuh Kelurahan Kampung Aur Kecamatan Medan Maimun Kota Medan - Salman Alfarisi; Rujiman Rujiman; T. Sabrina (Ekonomikawan: Jurnal Ilmu Ekonomi dan Studi Pembangunan, 2023)
The purpose of this study was to analyze the rejuvenation of the slum area of Kampung Aur Village and Hamdan Village, Medan Maimun District. The analytical method used is a quantitative descriptive method using primary data and secondary data. The indicators are clean water, drainage, sanitation, solid waste, roads, socio-economic community, age, education, gender, number of family dependents, length of stay in the area, and income. The analysis instrument is simple linear regression and SWOT. The results showed that the analysis of rejuvenation of slum areas had a positive effect on people's welfare, with a coefficient value of 0.667. others who were not included in this study. It is known that the value of Sig. = 0.000 0.05, it is concluded that village funds have a significant effect on community welfare. The right strategy is used in managing village funds for community welfare, namely a.) Recording land status and ownership; b) Rehabilitating settlement infrastructure; c) Increasing the government's role in the quality of the residential environment; d) Relocating people who live near river banks; e) Creating and encouraging the realization of healthy and sluggish settlement.